An examination of the traits and effects of "Red Songs" on education, Realistic inspiration and value, and culture during the Yan’an Period - Ma, Xiaoshuang (Edelweiss Applied Science and Technology, 2024)
To discuss several qualities as well as the influence ‘Red Songs’ had on education, realism promotion and cultural development in general of Yanan Period. During the Yan’an Period ‘Red Songs” were not merely songs; they have been weapons transforming political and cultural reality. The songs were also a tool for disseminating good communist ideas and encouraging feelings of patriotism, as well influencing realization inspiration values culture in the collective consciousness building; through their integration into education. Nevertheless, it should be clarified that if “Red Songs” were unifying in nature then there are reasons to believe those scripts had been associated with periods of upheaval later on especially period such as the Cultural Revolution which was divisive and deeply devastating for Chinese society. Embedded in the history of Chinese modernity, a series of social mobilisations has been implemented. Nonetheless, many of these initiatives have failed as a result the narrow focus on the intended audience and one-dimensional approach. There were significant achievements during the success of CCP revolution in mobilising society through red songs pf Yan ‘an era. It comes out of integration between theoretical Marxist conception applied to a given situation and the useful lessons drawn from former outcomes.